2019
DOI: 10.1080/23802359.2019.1612296
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of the traditional medicinal plant Stellera chamaejasme L. (Thymelaeaceae)

Abstract: Stellera chamaejasme is a toxic perennial herb found in open and dry places in East Asia and has the potential for new drugs for anti-inflammatory, analgesic, and cutaneous wound-healing purposes. Here, we present the complete chloroplast genome of S. chamaejasme. Its length is 173,381 bp and has four subregions; 86,769 bp of large-single-copy and 2,858 bp of small-single-copy regions are separated by 41,877 bp of inverted repeat regions, including 135 genes (89 protein-coding genes, 8 rRNAs, and 38 tRNAs). Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Phylogenetic analysis was performed to determine relatedness of the seven Aquilaria cp genomes sequenced in this study and four publicly available Aquilaria cp genomes: (1) A. crassna (MK779998) 23 , (2) A. sinensis (KT148967) 18 , (3) A. yunnanensis (MG656407) 25 , and (4) A. malaccensis (MH286934) 24 . To place Aquilaria in relation to other species in the family Thymelaeaceae, sequences from G. affinis and P. macrocarpa, and three available accessions: (1) Daphne tangutica (MK455880) 36 , (2) Daphne kiusiana (KY991380) 37 , and (3) Stellera chamaejasme (MK681211) 38 , were included. Neobalanocarpus heimii (MH746730) 39 and Eucalyptus grandis (HM347959) 40 were used as outgroups.…”
mentioning
confidence: 99%
“…Phylogenetic analysis was performed to determine relatedness of the seven Aquilaria cp genomes sequenced in this study and four publicly available Aquilaria cp genomes: (1) A. crassna (MK779998) 23 , (2) A. sinensis (KT148967) 18 , (3) A. yunnanensis (MG656407) 25 , and (4) A. malaccensis (MH286934) 24 . To place Aquilaria in relation to other species in the family Thymelaeaceae, sequences from G. affinis and P. macrocarpa, and three available accessions: (1) Daphne tangutica (MK455880) 36 , (2) Daphne kiusiana (KY991380) 37 , and (3) Stellera chamaejasme (MK681211) 38 , were included. Neobalanocarpus heimii (MH746730) 39 and Eucalyptus grandis (HM347959) 40 were used as outgroups.…”
mentioning
confidence: 99%
“…By comparing published cp genome reports on members of the Thymelaeaceae, it was determined that the complete cp genome sequence of Edgeworthia is shorter than those of G. affinis of subfamily Octolepidoideae (176,548 bp) and nine species of Aquilaria (Aquilaria beccariana, Aquilaria crassna, Aquilaria hirta, Aquilaria malaccensis, Aquilaria microcarpa, Aquilaria rostrata, A. sinensis, Aquilaria subintegra, and Aquilaria yunnanensis; 174,693-174,907 bp) from Aquilarieae of subfamily Thymelaeoideae (Hishamuddin et al, 2020), but was longer than the four species of Daphne (Daphne giraldii, D. kiusiana, Daphne laureola, and Daphne tangutica; 169,944-171,643 bp) (Cho et al, 2018;Könyves et al, 2019;Yan et al, 2019a,b), two species of Wikstroemia (W. chamaedaphne and Wikstroemia indica; 151,731-173,042 bp) from the Daphne group , and Pimelea aquilonia (172,364 bp) from the Gnidia group (Foster et al, 2018), all belonging to the Daphneae of subfamily Thymelaeoideae. Stellera chamaejasme, from the monospecific Stellera, was the only species from the Daphne group with a total cp genome size within the cp genome size range of Edgeworthia, which was 173,381 bp (Yun et al, 2019). Eventually, rather small size of the SSC region was observed in the cp genome of most species from Thymelaeaceae.…”
Section: Discussionmentioning
confidence: 99%
“…chamaedaphne and Wikstroemia indica ; 151,731–173,042 bp) from the Daphne group ( Qian and Zhang, 2020 ; Qian et al, 2020 ), and Pimelea aquilonia (172,364 bp) from the Gnidia group ( Foster et al, 2018 ), all belonging to the Daphneae of subfamily Thymelaeoideae. Stellera chamaejasme , from the monospecific Stellera , was the only species from the Daphne group with a total cp genome size within the cp genome size range of Edgeworthia , which was 173,381 bp ( Yun et al, 2019 ). Eventually, rather small size of the SSC region was observed in the cp genome of most species from Thymelaeaceae.…”
Section: Discussionmentioning
confidence: 99%
“…After getting first draft of chloroplast genome sequences, gap was filled with GapCloser v1.12 (Zhao et al, 2011) and all bases from the assembled sequences were confirmed using BWA v0.7.17 (Li, 2013) and SAMtools v1.9 (Li et al, 2009). All bioinformatic processes for de novo assembly was conducted by the pipeline, Genome Information System (GeIS; http://geis.infoboss.co.kr), which has been efficiently utilized and optimized in the previous studies (Min et al, 2019;Yun et al, 2019;Kim et al, 2021aKim et al, , 2021bPark et al, 2021b).…”
Section: De Novo Assembly and Annotation Of Diarthron Linifolium Chloroplast Genomementioning
confidence: 99%